Implementasi Corporate Social Responsibility Dalam Membangun Reputasi PT KAI (Persero) Doap 6 Palembang - Marleni (UIR Press, 2021)
This program is carried out to support the company's orientation which not only prioritizes material benefits, but also relationships. This study aims to find out the implementation of the corporate social responsibility program and the constraints experienced in the implementation of CSR PT KAI (Persero) Doap 6 Palembang. The population in this study were Pertamina equipment and CSR recipients, totaling 7 people. The sampling technique used in this research is descriptive with a qualitative approach. by taking agricultural equipment and CSR recipients as samples. Data processing in this study was carried out using a qualitative descriptive analysis. Direct observation of the object of research and interviews. The results of this study found that the implementation of CSR can boost the company's image by external relations PT PT KAI (Persero) Doap 6 Palembang and in line with public relations management. In this study, it can be concluded that the implementation of the CSR program carried out by PT. KAI (Persero) Daop 6 Palembang is varied and responsive, especially to respond to the needs of the community and the environment around the company. However, the implementation of this program is still in the realm of charity and service, not a manifestation of social investment.